Physical fitness characteristics of taekwondo athletes: a cross-sectional study - Yogi Setiawan; Muhammad Fakhrur Rozi; Pringgo Mardesia; Yogi Arnaldo Putra; Sari Mariati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aimed to analyze the physical fitness profile of Taekwondo athletes at Universitas Negeri Padang based on standardized fitness components. A descriptive quantitative design was employed involving 25 athletes (13 males and 12 females) selected through purposive sampling. Physical fitness was assessed using the Tes Kebugaran Jasmani Indonesia (TKJI), which includes speed (60-m sprint), upper-body strength (pull-ups/flexed-arm hang), abdominal endurance (sit-ups), explosive power (vertical jump), and cardiorespiratory endurance (1200-m/1000-m run). Data were analyzed using descriptive statistics (mean and standard deviation) and categorized according to TKJI norms. The results showed that male athletes had a mean score of 12.69 (SD = 2.56), while female athletes had a mean score of 12.00 (SD = 2.98). The majority of athletes were classified in the “poor” category (61.5% males; 41.7% females), indicating suboptimal fitness levels. In conclusion, the physical fitness profile of Taekwondo athletes in this setting is below expected standards, highlighting the need for more structured and sport-specific training programs to improve performance.